An Implemented of Intelligent Access Gate Control (IAGC) - Abu Samah, Aswandi (Universiti Teknologi Petronas, 2004)
The author's project is focusing on developing application on Intelligent Access Gate Control (IAGC) of UTP. The entrance gate in the UTP campus is chosen as the case study for this project. The aspects that will be covered are the features and the functionality of (IAGC). Another important element that has been considered on IAGC application is to provide online system on centralized source of information and data. Besides that, IAGC application also tends to provide a 'drive-thru' as well as it will eliminate waiting time due to long lines at the entrance gate. It is also helps in conserve fuel consumption, and ease traffic congestion. In accomplishing the project, the designed application for IAGC was modeled by using motor controlled infrared detector circuit as simulation. From this simulation, the complete prototype of IAGC was designed, which were used in designing the desired entrance access gate application for Security Department at UTP. Once the learning stage of the collected information and feedback has been completed, it is used as discussion for the feasible implementation of IAGC application.